Intestinal P‐gp and Putative Hepatic OATP1B Induction: International Transporter Consortium Perspective on Drug Development Implications. Issue 1 (9th July 2020) - Zamek‐Gliszczynski, Maciej J.; Patel, Mitesh; Yang, Xinning; Lutz, Justin D.; Chu, Xiaoyan; Brouwer, Kim L. R.; Lai, Yurong; Lee, Caroline A.; Neuhoff, Sibylle; Paine, Mary F.; Sugiyama, Yuichi; Taskar, Kunal S.; et al.
Abstract : There is an increasing interest in transporter induction (i.e., decreased systemic drug exposure due to increased efflux‐limited absorption or transporter‐mediated clearance) as a mechanism of drug–drug interactions (DDIs), although evidence of clinical relevance is still evolving. Intestinal P‐glycoprotein (P‐gp) and hepatic organic anion transporting polypeptides 1B (OATP1B) can be important determinants of drug absorption and disposition, as well as targets for DDIs. Current data indicate that intestinal P‐gp protein levels can be induced up to threefold to fourfold in humans primarily with pregnane X receptor (PXR) activators, and that this induction can decrease the systemic exposure of drugs with P‐gp efflux‐limited absorption (e.g., ≤ 67% decrease in the exposure of total dabigatran following rifampin multiple oral dosing). Evaluation of the clinical relevance of P‐gp induction as a DDI mechanism must consider the induction potential of the perpetrator drug for P‐gp and attenuation of exposure of the victim drug in the context of its therapeutic window. Practical drug development recommendations are provided herein. Reports are contradictory on OATP1B induction by PXR activators in human hepatocytes and liver biopsies. Some clinical investigations demonstrated that rifampin pretreatment decreased exposure of OATP1B substrates, while other studies found no differences, and the potential involvement of other mechanisms in these observed DDIs cannot be definitively ruled out. Thus, further studies are needed to understand hepatic OATP1B induction and potential involvement of other mechanisms contributing to reduced exposure of OATP1B substrates. This review critically summarizes the state‐of‐the‐art on intestinal P‐gp and hepatic OATP1B induction, and highlights implications for drug development.